2011
DOI: 10.1007/978-1-4614-9200-9_16
|View full text |Cite
|
Sign up to set email alerts
|

The Solar Wind in the Outer Heliosphere and Heliosheath

Abstract: The solar wind environment has a large influence on the transport of cosmic rays. This chapter discusses the observations of the solar wind plasma and magnetic field in the outer heliosphere and the heliosheath. In the supersonic solar wind, interaction regions with large magnetic fields form barriers to cosmic ray transport. This effect, the "CR-B" relationship, has been quantified and is shown to be valid everywhere inside the termination shock (TS). In the heliosheath, this relationship breaks down, perhaps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Voyager observations of the outer heliosphere are reviewed by Richardson et al . [, ] and Richardson and Burlaga [].…”
Section: Voyager Datamentioning
confidence: 99%
“…Voyager observations of the outer heliosphere are reviewed by Richardson et al . [, ] and Richardson and Burlaga [].…”
Section: Voyager Datamentioning
confidence: 99%
“…The subject of a strong variability of the B-field in the HS along the trajectory of V2 has been mentioned already [12]. There they reported that HS plasma and magnetic field were highly variable on scales as small as ten minutes.…”
Section: Journey and Trajectory Of The Sc In The Hs/the Intervals Selmentioning
confidence: 84%
“…Voyager 2 (V2) crossed the termination shock (TS) and entered the heliosheath in August 2007 during a time of decreasing solar activity [ Burlaga et al ., ]. Heliosheath observations of the plasma from 2007.7 to mid‐2010 and the magnetic field from 2007.7 to 2009.4 were reviewed by Richardson and Burlaga [].…”
Section: Introductionmentioning
confidence: 99%